2019
DOI: 10.1111/cbdd.13575
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of phenylpiperazine derivatives as potent anticancer agents for prostate cancer

Abstract: Novel thiourea (5a, 5b) and thiazolidinone derivatives (6a, 6b) were synthesized by hybridizing molecules starting from the compound 6‐(4‐phenylpiperazin‐1‐yl)pyridin‐3‐amine (4) which is known to show anticancer activity. The synthesis of the leading compound was carried out by using 1‐(5‐nitropyridin‐2‐yl)‐4‐phenylpiperazine (3) which was obtained by a novel method of the reaction of 2‐chloro‐5‐nitropyridine (1) and N‐phenylpiperazine (2). The structures of the compounds were confirmed using FTIR, 1H NMR, 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Interestingly, it was found that the treatment with this steroid oxime (50 µM, 24 h) induced a G 2 /M cell cycle arrest of LNCaP cells ( Figure 5 ). Also, LNCaP cells were not able to pass through to the S and G 2 /M phases treated by compound 5-FU, which is in agreement with literature for these cells [ 42 ].…”
Section: Resultssupporting
confidence: 90%
“…Interestingly, it was found that the treatment with this steroid oxime (50 µM, 24 h) induced a G 2 /M cell cycle arrest of LNCaP cells ( Figure 5 ). Also, LNCaP cells were not able to pass through to the S and G 2 /M phases treated by compound 5-FU, which is in agreement with literature for these cells [ 42 ].…”
Section: Resultssupporting
confidence: 90%
“…In order to determine the effect of USP7 suppression on the control of cell division, T47D and MCF7 cells were subjected to cell cycle analysis according to the protocol (Demirci et al, 2019). Briefly, cells were plated (3 × 10 5 cells/well) in 6-well tissue culture plates; after 24 h incubation, siRNA or p5091 was applied to the cells.…”
Section: Cell Cycle Analysismentioning
confidence: 99%
“…The pharmacological properties of phenylpiperazines and their derivatives have been described by various researchers (Cohen et al 1982;Conrado et al 2010;Neves et al 2003;Hanano et al 2000). The design and synthesis of phenylpiperazine derivatives as potent anticancer agents for prostate cancer have been reported (Demirci et al, 2019). Many pharmaceutical compounds are derived from 1-phenyl-piperazine, including oxypertine (Archer et al, 1962), trazodone (Alhaider, 1992) and nefazodone.…”
Section: Chemical Contextmentioning
confidence: 99%